Functional reconstruction of bovine P450scc steroidogenic system in Escherichia coli - Makeeva, Desislava S.; Dovbnya, Dmitry V.; Donova, Marina V.; Novikova, Ludmila A. (Scientific Research Publishing, 2013)
Mammalian cytochrome P450scc enzyme system catalyzes the initial step in steroid hormone biosynthesis—cholesterol hydroxylation followed by cleavage of the side-chain to yield pregnenolone. This system consists of three components—the cytochrome P450scc (CYP11A1), a flavoprotein (NADPH-adrenodoxin reductase, AdR) and an iron-sulfur protein (adrenodoxin, Adx). In this work, the three-component electron transport chain (AdR/Adx/CYP11A1) from bovine adrenal cortex has been implemented in Escherichia coli by co-expression of the corresponding coding sequences from a tricistronic plasmid. The cDNAs of AdR, Adx and CYP11A1 are situated in a single transcription unit and separated by ribosome binding sequences. The recombinant strain created was capable of synthesizing functional proteins identical to the bovine CYP11A1, AdR and Adx on molecular weights and immuno-specificity. The experiments in vivo showed pregnenolone production from cholesterol by the transformed bacteria. Maximal productivity of 0.42 ± 0.015 mg/l pregnenolone for 24 h has been reached for the induced cells in the presence of cholesterol solubilizing agent—methyl-β-cyclodextrin. Thus, a stable transgenic E. coli strain with the functional reconstructed bovine cholesterol side-chain cleavage system has been firstly generated in this work. The findings are of importance for studies of mammalian steroidogenic system features, and may open some perspectives for further generation of novel microbial biocatalysts.
Keywords: Cytochrome P450; CYP11A1; Adrenodoxin; Adrenodoxin Reductase; Steroid Hormone Biosynthesis; Heterologous Expression